Balanced Fertilization with Nitrogen, Molybdenum, and Zinc: Key to Optimizing Pecan Tree Yield and Quality of Western Schley Pecan Tree - Laura R. Orozco-Meléndez; Linda C. Noperi-Mosqueda; Julio C. Oviedo-Mireles; Nubia G. Torres-Beltrán; Rosa M. Yáñez-Muñoz; Juan M. Soto-Parra (Horticulturae)
This study evaluated the effect of soil and foliar fertilization with nitrogen (N), molybdenum (Mo), zinc (Zn), and their combination (Zn-Mo) on nutrition, enzymatic activity, photosynthetic pigments, and productive parameters in the Western Schley pecan tree. An orthogonal Taguchi L16 design was used with differentiated soil and foliar nitrate concentrations, reaching an average of 1557.7 mg kg−1, and increasing up to 1907 mg kg−1 depending on the fertilization dose. Nitrate reductase activity (NRNO3−) significantly increased with N and Mo applications, reaching a maximum of 13.62 µmol. Among photosynthetic pigments, chlorophyll a was the only variable with a significant response, highlighting the role of Mo in its enhancement. Positive effects were also observed on pomological traits such as yield (up to 425 kg ha−1), nut weight, and kernel percentage with increased doses of N and Mo. In conclusion, combined fertilization improved the nutritional status, physiological responses, and productivity of pecan trees, emphasizing the importance of balanced nutrient management to avoid nutritional antagonisms and to optimize both yield and fruit quality.